Lateral Forehead Flap in Neglected Giant Basal Cell Carcinoma of the Nose: A Case Report - Jonathan Kevin; Renate Parlene Marsaulina; Alberta Jesslyn Gunardi; Irena Sakura Rini (National Cancer Center - Dharmais Cancer Hospital, 2019)
Introduction: Neglected basal cell carcinoma (BCC) of the nose can grow into giant BCCs, rare cases with extensive nasal defects. Such large defects would require complex reconstruction such as free flaps or multiple local flaps. Lateral forehead flap may provide a simpler alternative with good functional and cosmetic results.Case Presentation: We present a case of a 76-year-old man with neglected giant BCC of nose extending to right lower eyelid and upper lip. Wide excision of the tumor leaves a 12cm x 10cm defect. Reconstruction was performed using lateral forehead flap and donor site was covered with split-thickness skin graft from thigh. The second surgery was done after four months to create nostrils and wider eye-opening. Six months later, flap was viable and there was no sign of recurrence. Nasal reconstruction is planned to further improve cosmetics. In this case, neglect is due to low social-economic status and adaptation to painless tumors. The use of lateral forehead flap allows for simpler and faster surgery suitable for elderly. Delayed reconstruction was needed to ensure optimal tissue healing. Conclusions: Neglected BCC causes disfigurement with remarkable morbidity, requiring complex reconstruction. The lateral forehead flap is a simple and reliable reconstruction method for extensive nasal defects with good functional and cosmetic outcomes.